PERAN UNI EROPA MELALUI PATROLI EU NAVFOR DALAM MENANGANI AKTIVITAS PEROMPAK SOMALIA DI TELUK ADEN PERIODE TAHUN 2008-2012 - Mustika, Michelle May; Dir, Andi Akhmad Basith (Journal of International Relations, 2019)
Somali pirates activities in the Gulf of Aden have become an international security threat. Moreover, every countries which involved in international sea trade are also affected with the disadvantage impacts in economic sector. Recognizing the existence of these international security threats and losses, The United Nations is released a mandate for every member countries to contributing on handling the Somali pirates issue in the Gulf of Aden. With this mandate, the European Union is showing its active role to handling the Somali pirates issue. The European Union’s role have been realized through the assignment of EU NAVFOR Patrols since 2008. This research used qualitative methods alongside with international issue and European norms as a conceptual base, to explain the European Union’s role in the Gulf of Aden especially from the assignment of EU NAVFOR Patrols. The result of this research indicated that the European Union’s role with the assignment of EU NAVFOR patrols has an impact on reducing the number of Somali pirates activity and ship attacked by the Somali pirates.